Efficacy of buprofezin, pyriproxyfen and spirotetramat against Bemisia tabaci MEAM1 nymphal field populations in Florida. (November 2021) - Rossitto De Marchi, Bruno; Smith, Hugh
Abstract: The whitefly, Bemisia tabaci MEAM1 (Gennadius) (Hemiptera: Aleyrodidae) is a major pest of vegetable crops in the USA, causing yield losses through transmission of plant viruses and induction of plant disorders. Irregular ripening of tomato and silvering of squash leaves are whitefly-induced plant disorders associated with B. tabaci nymphal feeding. Insecticides applied to manage B. tabaci nymphs and these plant disorders include insect growth regulators (IGRs) and lipid biosynthesis inhibitors. Eleven B. tabaci MEAM1 field populations were collected from vegetables and weeds in south Florida in 2019–2020 to assess the efficacy of nymphal insecticides using a maximum dose bioassay. A susceptible laboratory colony of B. tabaci MEAM1 and a colony of B. tabaci MED were also tested. Among the field populations, spirotetramat was the least efficient product for reducing adult emergence and pyriproxyfen and buprofezin were both highly effective. In contrast to the field populations, the lab MED colony was highly susceptible to spirotetramat while pyriproxyfen and buprofezin demonstrated low efficacy for reducing adult emergence. The results indicate that tolerance to spirotetramat may be present in field populations of B. tabaci . Highlights: Tolerance to spirotetramat may be developing among whitefly populations in Florida. Susceptibility to pyriproxyfen and buprofezin was reported. Integrated pest management strategies are needed to conserve insecticide efficacy.